UV filters and their impact on marine life: state of the science, data gaps, and next steps. (23rd June 2022) - Lebaron, P.
Abstract: Sunscreens containing broad‐spectrum ultraviolet (UV) filters play an essential role in protecting the skin against the damage induced by sun overexposure. However, the widespread use of sunscreens and other personal care products containing these filters has led to these compounds being widely detected in the environment and being identified as emerging pollutants in marine waters. Concerns raised by laboratory studies investigating the potential impact of UV filters on coral communities have already led to bans on the use of some sunscreens in a few tourist hotspots. Although UV filter pollution may be just one of the many environmental factors impacting coral health worldwide, the media attention surrounding these studies and the legislative changes may lead patients to question dermatologists about the environmental safety of some sunscreen products. This review provides an overview of current knowledge on the impact of UV filters on marine ecosystems, concentrating on recent studies examining the effects of commonly used filters on organisms at low trophic levels and of how alternative approaches, such as metabolomics, can be used to further assess UV filter ecotoxicity. Current gaps in our knowledge are also discussed, most notably the need to increase our understanding of the longer‐term fate and behaviour of UV filters in the marine environment, develop more adapted standardized ecotoxicity tests for a wider range of marine species, and evaluate the impact of UV filters on the marine food web. We then discuss future perspectives for the development of new, more environmentally friendly, filters that may enable the use of the most toxic compounds to be reduced without compromising the effectiveness of sunscreen formulations. Finally, we consider how dermatologists play a key role in educating patients on the need for a balanced approach to sun exposure, sun protection, and conservation of the marine environment.